2015 Pediatric Research Priorities in Prehospital Care. (3rd May 2016) - Browne, Lorin R.; Shah, Manish I.; Studnek, Jonathan R.; Farrell, Brittany M.; Mattrisch, Linda M.; Reynolds, Stacy; Ostermayer, Daniel G.; Brousseau, David C.; Lerner, E. Brooke
Abstract: Background: Pediatric prehospital research has been limited, but work in this area is starting to increase particularly with the growth of pediatric-specific research endeavors. Given the increased interest in pediatric prehospital research, there is a need to identify specific research priorities that incorporate the perspective of prehospital providers and other emergency medical services (EMS) stakeholders.Objectives: To develop a list of specific research priorities that is relevant, specific, and important to the practice of pediatric prehospital care.Methods: Three independent committees of EMS providers and researchers were recruited. Each committee developed a list of research topics. These topics were collated and used to initiate a modified Delphi process for developing consensus on a list of research priorities. Participants were the committee members. Topics approved by 80% were retained as research priorities. Topics that were rejected by more than 50% were eliminated. The remaining topics were modified and included on subsequent surveys. Each survey allowed respondents to add additional topics. The surveys were continued until all topics were either successfully retained or rejected and no new topics were suggested.Results: Fifty topics were identified by the three independent committees. These topics were included on the initial electronic survey. There were 5 subsequent surveys. At the completion of the final survey a total of 29 research priorities were identified. These research priorities covered the following study areas: airway management, asthma, cardiac arrest, pain, patient-family interaction, resource utilization, seizure, sepsis, spinal immobilization, toxicology, trauma, training and competency, and vascular access. The research priorities were very specific. For example, under airway the priorities were: "identify the optimal device for effectively managing the airway in the prehospital setting" and "identify the optimal airway management device for specific disease processes."Conclusion: This project developed a list of relevant, specific, and important research priorities for pediatric prehospital care. Some similarities exist between this project and prior research agendas but this list represents a current, more specific research agenda and reflects the opinions of working EMS providers, researchers, and leaders.Key words: emergency medical technician; research; emergency medical services; priorities